Pengembangan Model Inovasi Bahan Ajar Pendidikan Agama Islam Berbasis Aplikasi Canva di SMK Alwashliyah Jakarta: Penelitian - Kurniawan, Jefri; Fariiz, Abdurrahman; Safiuddin (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to develop digital-based Islamic Religious Education (PAI) teaching materials using the Canva application to improve learning effectiveness at SMK Al Washliyah Jakarta. The background of the study is based on the low interest and motivation of students in PAI due to unattractive conventional learning methods and the lack of visual media. The study used a Research and Development (R&D) approach with the ADDIE development model that includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects included PAI teachers and 11th-grade students of the AKL, MP1, and MP2 programs. Data collection instruments consisted of interviews, questionnaires, and tests. The results of expert validation showed that the Canva teaching materials had a